AḤKĀM AL-JARAḤ MANUSCRIPT: TEXT EDITING AND CENTRAL IDEAS STUDY - Jannah, Raudhatul; Firdaus, Thoriqi (Pusat Riset Manuskrip, Literatur, dan Tradisi Lisan, 2023)
The Aḥkām al-Jaraḥ manuscript is one of the Malay-Jawi manuscripts which contains jaraḥ law. This manuscript is from the Philological Collection of the Aceh Museum with inventory number 07,737, in a collection of texts totalling 54 pages. The text of Aḥkām al-Jaraḥ is on pages 28 to 48. The condition of the manuscript is old; it is feared that it could experience further damage, and the contents of the manuscript will be lost. This research aims to produce text edits so that the manuscript can be read correctly because the Aḥkām al-Jaraḥ text is only found in one manuscript (codex unicus). The method used is single manuscript research with a critical edition of the text and analysis of central ideas. The central ideas contained in the Aḥkām al-Jaraḥ manuscript include an explanation of the fundamental law of wounds, the law of intentional and unintentional murder, the division of types of murder, sanctions for murderers and members taken by qiṣāṣ. The results of the research show that first, editing the text with a critical edition, and second, knowing clearly and in detail the contents of the Aḥkām al-Jaraḥ manuscript, which contains Islamic teachings about jaraḥ law.